An anti-dust finishing agent for silk fabrics, and a preparation method and application thereof

CN122980211APending Publication Date: 2026-10-27ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611469075.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但在实际应用中,三聚氯氰活性过高,导致其储存稳定性差、使用安全性低,且水溶性不佳,难以在水中均匀分散,影响与纤维的交联效果

Benefits of technology

本发明以三聚氯氰、特定含羟基的亲水有机物,以及水溶性有机溶剂为制备原料,在一定比例下形成了一种具有适度反应活性、水分散性得到改善的整理剂原液,即为用于真丝织物的防灰伤整理剂。使用时,可将该原液在水中分散,所述水溶性有机溶剂的存在不仅能提高活性组分在水相中的分散性,而且减缓了其与水分子的副反应,从而确保活性组分能有效与真丝纤维发生交联。经本发明整理剂和方法处理后的真丝织物,防灰伤效果显著,经多次水洗后外观良好,纤维原纤化现象被大大降低,且较好地保持了织物原有手感。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122980211A_ABST
    Figure CN122980211A_ABST
Patent Text Reader

Abstract

The application discloses a kind of anti-dust damage finishing agent for real silk fabric and its preparation method and application, belong to textile finishing technical field.The preparation raw material of the anti-dust damage finishing agent includes tricyanogen chloride, hydroxyl-containing hydrophilic organic matter and water-soluble organic solvent;The mass percentage concentration of tricyanogen chloride relative to water-soluble organic solvent is 10~30%;The water-soluble organic solvent is selected from one or more of acetone, dimethyl sulfoxide, tetrahydrofuran and 1,4-dioxane;The hydroxyl-containing hydrophilic organic matter is selected from one or more of sodium p-benzenesulfonic acid, sodium hydroxyacetate and oligomeric ethylene glycol monomethyl ether.The prepared anti-dust damage finishing agent is applied to real silk fabric anti-dust damage finishing, has good anti-dust damage effect, and higher safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of textile finishing technology, specifically to a cyanuric chloride-based anti-scratching finishing agent and its preparation method, as well as the application of this finishing agent in anti-scratching finishing of dyed or undyed silk textile materials. Background Technology

[0002] Silk is a natural protein fiber formed from the solidified silk fluid secreted by mature silkworms during cocoon spinning, rich in various amino acids. Refined silk fibers generally possess excellent skin-friendliness and breathability, with a smooth surface and bright luster. However, the internal structure of silk fibers consists of many interwoven fibrils forming a mesh-like structure. The bonding force between these fibrils is relatively weak, making them prone to separation and fibrillation during dry or wet friction during wear or machine washing. This results in a rough fabric surface and defects or damage such as whitening or a dull gray color. This problem, commonly known as "gray damage," has long led to silk fabrics being considered delicate and typically only dry-cleanable, significantly limiting the application range of silk textiles.

[0003] To address the issue of graying on silk fabrics, there are currently two main finishing methods. One method uses softeners to reduce surface friction of the silk fibers, offering some protection against graying, but its durability is poor. The other method uses chemical cross-linking to enhance the bonding between the fibrils, aiming for permanent protection against graying. Commonly used cross-linking agents include dimethyloldihydroxyvinyl urea resin (2D resin) and polycarboxylic acids. However, the anti-graying effect of existing finishing agents remains limited, and the finishing process significantly affects the fabric's hand feel; furthermore, 2D resin finishing also presents formaldehyde release issues, failing to meet environmental protection requirements.

[0004] Furthermore, cyanuric chloride contains highly reactive chlorine groups, which can react with active groups such as amino (-NH2) or hydroxyl (-OH) groups on silk fibers to achieve chemical cross-linking; some studies have reported its use in finishing silk fabrics. However, in practical applications, cyanuric chloride's high reactivity leads to poor storage stability, low safety in use, and poor water solubility, making it difficult to disperse evenly in water and affecting the cross-linking effect with fibers. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide an anti-smudge finishing agent for silk fabrics, its preparation method, and its application. The anti-smudge finishing agent provided by the present invention has good anti-smudge effect and high safety.

[0006] This invention provides an anti-smudge finishing agent for silk fabrics, the raw materials for which include cyanuric chloride, hydrophilic organic compounds containing hydroxyl groups, and water-soluble organic solvents; The cyanuric chloride has a mass percentage concentration of 10%-30% relative to the water-soluble organic solvent; the water-soluble organic solvent is selected from one or more of acetone, dimethyl sulfoxide, tetrahydrofuran, and 1,4-dioxane. The hydroxyl-containing hydrophilic organic compound is selected from one or more of sodium p-phenolsulfonate, sodium glycolate, and oligomeric polyethylene glycol monomethyl ether; the molar ratio of the hydroxyl-containing hydrophilic organic compound to cyanuric chloride is 0.8:1 to 1.2:1.

[0007] The present invention provides a method for preparing the anti-scratching finishing agent as described above, which includes the following steps: dispersing cyanuric chloride in a water-soluble organic solvent, adding a hydrophilic organic compound containing hydroxyl groups under stirring conditions to react and obtain the anti-scratching finishing agent.

[0008] This invention provides a method for finishing silk fabrics, which includes the following steps: The anti-smudge finishing agent is dispersed in water to form a finishing working solution, which is then applied to the silk fiber material to be treated. After finishing, the finished silk fabric is obtained.

[0009] Preferably, the silk fiber material to be treated is an undyed fabric, a dyed fabric, or a printed fabric.

[0010] Preferably, the finishing working solution is adjusted to pH 6-8, impregnates the silk fiber material to be treated, and is heated to 40-60°C for finishing. After rinsing and drying, the finished silk fabric is obtained.

[0011] Compared with the prior art, the present invention has the following beneficial effects: This invention uses cyanuric chloride, specific hydrophilic organic compounds containing hydroxyl groups, and water-soluble organic solvents as raw materials to form a finishing agent stock solution with moderate reactivity and improved water dispersibility in a certain proportion, which is a finishing agent for preventing graying on silk fabrics. In use, the stock solution can be dispersed in water. The presence of the water-soluble organic solvent not only improves the dispersibility of the active components in the aqueous phase but also slows down the side reactions with water molecules, thereby ensuring that the active components can effectively cross-link with the silk fibers. Silk fabrics treated with the finishing agent and method of this invention show significant anti-graying effects, maintain a good appearance after multiple washes, greatly reduce fiber fibrillation, and better preserve the original hand feel of the fabric.

[0012] Furthermore, the finishing method for silk fabrics in this invention is simple, releases no formaldehyde, and is safe and environmentally friendly. Therefore, this invention solves the problems of poor performance of anti-smudge finishing agents, significant impact on the feel of silk, and formaldehyde release in existing technologies. Attached Figure Description

[0013] Figure 1This is a microscopic diagram of the fibrillation state of the untreated sample in Example 1 after 10 machine washes; Figure 2 This is a microscopic image of the fibrillation state of the sample treated in Example 1 after 10 machine washes. Figure 3 This is a microscopic image of the fibrillation state of the treated sample after 10 machine washes in Example 2. Figure 4 This is a microscopic diagram of the fibrillation state of the commercially available treated sample in Example 1 after 10 machine washes. Figure 5 This is a microscopic diagram of the fibrillation state of the sample treated with the present invention in Comparative Example 1 after 10 machine washes. Figure 6 This is a microscopic diagram of the fibrillation state of the treated sample in Comparative Example 2 after 10 machine washes. Detailed Implementation

[0014] The technical solutions in the embodiments of this application are described clearly and completely below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0015] This invention provides an anti-smudge finishing agent for silk fabrics, the raw materials for which include cyanuric chloride, hydrophilic organic compounds containing hydroxyl groups, and water-soluble organic solvents; The cyanuric chloride has a mass percentage concentration of 10%-30% relative to the water-soluble organic solvent; the water-soluble organic solvent is selected from one or more of acetone, dimethyl sulfoxide, tetrahydrofuran, and 1,4-dioxane. The hydroxyl-containing hydrophilic organic compound is selected from one or more of sodium p-phenolsulfonate, sodium glycolate, and oligomeric polyethylene glycol monomethyl ether; the molar ratio of the hydroxyl-containing hydrophilic organic compound to cyanuric chloride is 0.8:1 to 1.2:1.

[0016] The anti-scratching finishing agent provided by this invention has sufficient finishing reaction activity, can achieve good anti-scratching effect, and has a certain degree of stability and high safety.

[0017] The main raw material of the anti-scratching finishing agent described in this embodiment of the invention is cyanuric chloride, which is the active core of the finishing agent. Cyanuric chloride, also known as 2,4,6-trichloro-1,3,5-triazine, has the molecular formula C3Cl3N3, is industrial grade, and is slightly soluble in water.

[0018] The anti-scratching finishing agent is in the form of a liquid finishing agent, and its preparation raw materials include a specific water-soluble organic solvent. The water-soluble organic solvent is a water-soluble, inert solvent that does not chemically react with cyanuric chloride, selected from one or more ketones, sulfones, ethers, and esters, and further selected from ketones, sulfones, and ethers. More preferably, it is selected from one or more acetone, dimethyl sulfoxide, tetrahydrofuran, and 1,4-dioxane. This water-soluble organic solvent serves both as a reaction medium and as an aid in the dispersion of functional molecules in water, and also mitigates side reactions with water molecules, thereby improving the anti-scratching finishing efficiency.

[0019] In preparing the anti-scratching finishing agent according to the embodiments of the present invention, the cyanuric chloride can be first dispersed in a water-soluble organic solvent, and a hydroxyl-containing hydrophilic organic compound can be added under stirring conditions to react, thereby obtaining the final product. The hydroxyl-containing hydrophilic organic compound generally has a single-terminal hydroxyl group and a hydrophilic group. Its hydroxyl end is used to react with the cyanuric chloride, thereby indirectly grafting it onto the surface of the silk fiber through the cyanuric chloride. The hydrophilic groups such as sulfonic acid groups, carboxyl groups, or polyethylene glycol chains contained in its molecule are used to bind water molecules and form a hydrated layer on the fiber surface. The compound can be selected from one of hydroxyl-containing sulfonates, hydroxyl-containing carboxylates, and oligomeric polyethylene glycol monoalkyl ethers, or a mixture of two or more compounds.

[0020] In some preferred embodiments, the hydroxyl-containing hydrophilic organic compound is selected from one or more of hydroxybenzene sulfonates, hydroxyalkyl sulfonates, hydroxybenzene carboxylates, hydroxyalkyl carboxylates, and polyethylene glycol monomethyl ether; including but not limited to: sodium p-phenol sulfonate, sodium glycol acetate, polyethylene glycol monomethyl ether (molecular weight Mn is about 350) / diethylene glycol monomethyl ether.

[0021] In the reaction system described in this embodiment of the invention, the mass percentage concentration of cyanuric chloride in the water-soluble organic solvent is 10%-30%. Specifically, 18-19 g of cyanuric chloride can be added to 120-150 mL of water-soluble organic solvent as a dispersion medium, and the mixture can be stirred and dispersed under low-temperature conditions, such as by cooling to 0-5 °C using an ice-water bath; the mass percentage concentration of cyanuric chloride is calculated based on this dispersion medium.

[0022] Furthermore, in the reaction system, the molar ratio of the hydroxyl-containing hydrophilic organic compound to cyanuric chloride is 0.8:1 to 1.2:1, for example, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1.

[0023] The synthesis process of the anti-scratching finishing agent described in this embodiment of the invention specifically includes: A dispersion of cyanuric chloride was prepared using a water-soluble organic solvent under low temperature and stirring conditions. Under stirring conditions, a solution of a hydrophilic organic compound containing hydroxyl groups dissolved in the water-soluble organic solvent is added dropwise to the dispersion, with the dropping rate controlled. After the addition is complete, the temperature can be raised to 30-35 °C, and the reaction can continue for 3-4 hours. After the reaction is complete, a dispersion containing functional or active molecules is obtained, which is the anti-dust finishing agent (stock solution).

[0024] The present invention further provides the application of the above-mentioned anti-smudge finishing agent or the anti-smudge finishing agent prepared by the above method in anti-smudge finishing of silk fiber materials.

[0025] Specifically, it provides a method for finishing silk fabrics, including the following steps: dispersing the anti-smudge finishing agent in water to form a finishing working solution, and applying it to the silk fiber material to be treated, and then finishing the silk fabric.

[0026] The finishing working solution described in this embodiment of the invention contains an anti-smudge finishing agent, which is used to finish undyed, dyed or printed silk fibers and their interwoven materials to give them anti-smudge properties that are resistant to machine washing, without affecting the hand feel of the silk fiber fabric.

[0027] The finishing method for preventing dust damage to silk fabrics described in some embodiments of the present invention is as follows: a. Preparation of finishing solution: Disperse the above-mentioned anti-smudge finishing agent in water to form a finishing solution; b. Impregnation treatment: Adjust the pH value to 6-8, place the silk fabric to be treated in the finishing working solution, and heat to 40-60 ℃ for finishing; c. Rinsing and drying: Rinsing and drying the treated fabric.

[0028] In the embodiments of the present invention, there are no special restrictions on the specifications of the silk fiber material to be treated; it can be an undyed fabric or a dyed or printed fabric (the type of color and the printed pattern are not limited).

[0029] The fiber fineness and fabric structure of the silk fiber material are also conventional; some embodiments use emerald green silk satin as the fabric material to be treated. Silk satin is commonly referred to as plain crepe satin, belonging to the satin weave fabric category, specifically a five-end satin weave; it is conventionally woven with pure mulberry silk (such as 2D, 20D, or 22D white raw silk). For the specifications of the silk fabric to be treated, its weight can be 8-30 momme, preferably 12-22 momme; the warp density is generally above 100 threads / cm; the yarn fineness can be 2D, 20D, or 22D mulberry silk. Furthermore, specific specifications can be conventionally adjusted according to the fabric type (plain crepe satin, double crepe, power spinning, etc.).

[0030] In some embodiments of the present invention, baking soda is added to the finishing working solution containing the anti-smudge finishing agent to adjust the pH value to 6-8, and the silk fabric to be treated is placed in the solution and subjected to a finishing reaction for 30-40 minutes. After the reaction is completed, the treated silk fabric is washed twice in water at 40-50°C, and finally dried at 110-130°C to obtain the anti-smudge finishing silk fabric.

[0031] In this embodiment of the invention, the anti-smudge treatment of silk crepe satin and other textile materials results in a lustrous surface and no obvious smudges after 10 machine washes. It exhibits significant anti-smudge effect, minimal impact on hand feel, and high safety.

[0032] The present invention is further illustrated below with specific embodiments, but these embodiments do not limit the scope of the invention in any way. Unless otherwise stated, the reagents used in the specific embodiments can be obtained by commercial means or conventional experimental methods.

[0033] Example 1

[0034] Synthesis: 18.5 g of cyanuric chloride was added to 120 mL of acetone and stirred to disperse. The mixture was then cooled to 0–5 °C in an ice-water bath. Under stirring, a solution of 35 g of oligomeric polyethylene glycol monomethyl ether (Mn≈350) dissolved in 30 mL of acetone was slowly added dropwise, controlling the dropping rate. The addition was completed in approximately 1 hour. After the addition was complete, the ice-water bath was removed, and the temperature was raised to 30–35 °C. The reaction was continued for 3–4 hours. After the reaction was completed, an acetone dispersion containing functional molecules was obtained, which is the undissolved anti-dust finishing agent (referred to as anti-dust agent).

[0035] In this embodiment, the finishing process for preventing dust damage to silk fabrics includes the following steps: (1) Provide the silk fabric to be treated: Emerald green silk satin.

[0036] (2) Treatment of silk fabric: Disperse 0.142g of the synthesized anti-ash agent in 56.6mL of water, add baking soda to adjust the pH to 8, and then soak 2.83g of the silk fabric to be treated for 40min. After the reaction is completed, wash the treated silk fabric twice in water at 45℃, and finally set and dry it at 130℃ to obtain anti-ash-damage silk fabric.

[0037] In this embodiment, the plain crepe satin treated with the anti-dust agent had a glossy surface and no obvious dust damage after 10 machine washes; while the untreated plain crepe satin had a severely dusty surface and lost its luster after washing.

[0038] The fibrillation status of the two silk fabric samples was observed using a scanning electron microscope. It was found that the untreated sample showed obvious fiber breakage and fuzziness on the surface, and the fabric appearance was noticeably grayish. Figure 1As shown; however, the samples treated with the anti-dust agent exhibited fewer fiber fuzz on the surface, less fibrillation, and no obvious dusting, as indicated. Figure 2 As shown. (Through) Figure 1 (untreated sample) and Figure 2 A detailed comparison of the (treated samples) clearly demonstrates the superior effects of this invention.

[0039] Example 2

[0040] The synthesis steps of the anti-dust agent include: adding 18.5 g of cyanuric chloride to 150 mL of dimethyl sulfoxide, stirring to disperse, and cooling in an ice-water bath to 0-5 °C. Under stirring conditions, slowly adding a solution of 23.6 g of sodium p-phenolsulfonate dissolved in 40 mL of dimethyl sulfoxide, controlling the reaction temperature not to exceed 5 °C, and continuing the reaction for 2 h after the addition is complete. After the reaction is complete, a dimethyl sulfoxide dispersion containing functional molecules is obtained, which is the stock solution of the anti-dust finishing agent.

[0041] In this embodiment, the finishing process for preventing dust damage to silk fabrics includes the following steps: (1) Provide the silk fabric to be treated: Emerald green silk satin.

[0042] (2) Anti-smudge treatment for silk fabrics: Disperse the above-mentioned anti-smudge finishing agent stock solution in water to prepare a finishing working solution, controlling the effective dosage of the finishing agent to be 2 g / L and the bath ratio to be 1:20. Adjust the pH of the working solution to 7-8 with baking soda, immerse the silk fabric to be treated in the solution, raise the temperature to 45-60 ℃, and soak for 40 min. After treatment, remove the fabric, rinse it twice with clean water, dehydrate it, and dry it at 80 ℃.

[0043] In this embodiment, after 10 machine washes, the silk fabric treated with the anti-dust agent showed minimal fiber peeling and breakage under an electron microscope, with little fibrillation. For specific results, please refer to [link to relevant documentation]. Figure 3 The treated silk fabric exhibits significantly reduced fibrillation on its surface, maintains a good appearance after multiple washes, and has a soft hand feel.

[0044] Comparative Example 1

[0045] Treatment with commercially available finishing agents: Take one sample of silk crepe satin, weighing 3.0 g. Prepare the finishing solution: Disperse a commercially available machine-washable finishing agent (2.0 g / L) in deionized water, adjust the pH to 8.0±0.2, and use a liquor ratio of 1:20. Immerse the sample in the finishing solution and heat to 60 ℃ for 40 minutes. After treatment, remove the fabric, rinse twice with clean water, dehydrate, and dry at 80 ℃.

[0046] Take a sample of silk crepe satin, weighing 3.0 g. Prepare the finishing working solution: Add 18.5 g of cyanuric chloride to 150 mL of dimethyl sulfoxide, stir to disperse, and cool in an ice-water bath to 0-5 °C. Under stirring conditions, slowly add a solution of 9.8 g of sodium glycolate dissolved in 30 mL of dimethyl sulfoxide, controlling the dropping rate, and complete the addition in about 1 hour. After the addition is complete, remove the ice-water bath, raise the temperature to 30-35 °C, and continue the reaction for 3-4 hours. After the reaction is complete, a dimethyl sulfoxide dispersion containing functional molecules is obtained, which is the stock solution of the anti-smudge finishing agent.

[0047] The above-mentioned anti-smudging finishing agent stock solution was dispersed in water to prepare a finishing working solution, with the effective dosage of the finishing agent controlled at 2 g / L and the bath ratio at 1:20. The pH of the working solution was adjusted to 7-8 with anhydrous sodium carbonate, and the silk crepe satin was immersed in the solution, heated to 60 ℃ and kept immersed for 40 min. After treatment, the fabric was removed, rinsed twice with clean water, dehydrated, and dried at 80 ℃.

[0048] The plain crepe satin treated with the commercially available anti-dust agent in Comparative Example 1 showed a glossy surface after 10 machine washes, with only a small amount of dust damage. Figure 4 As shown. Plain crepe satin treated with the anti-dust agent of this invention exhibits a lustrous surface and almost no dust damage after 10 machine washes, as... Figure 5 As shown. And through Figure 4 and Figure 5 In a specific comparison, namely the effect of commercially available anti-dust finishing agents and the finishing agent of the present invention, the surface fibers of the sample treated with the finishing agent of the present invention showed less fuzziness and almost no fibrillation.

[0049] The above machine washing was performed on the products of the above embodiments according to the washing methods described in GB / T 8629-2017 "Home Washing and Drying Procedures for Textile Testing".

[0050] Comparative Example 2

[0051] The synthesis steps are basically the same as in Example 1, except that: no hydrophilic organic compound containing hydroxyl groups is added (i.e., the step of adding oligomeric polyethylene glycol monomethyl ether is omitted), and only 18.5 g of cyanuric chloride is added to 120 mL of acetone, and the mixture is stirred and dispersed under the condition of cooling to 0~5 ℃ in an ice water bath. Then, the temperature is raised to 30~35 ℃ and stirring is continued for 3~4 h to obtain an acetone dispersion of cyanuric chloride.

[0052] Furthermore, the finishing process is the same as in Example 1.

[0053] The obtained treated sample and the treated sample of Example 1 were machine washed 10 times according to the "GB / T 8629-2017 Textiles - Test Procedures for Household Washing and Drying" standard. The fibrillation status of the fabric surface was observed using a scanning electron microscope (SEM). Figure 6The results show that the surface fibers of the sample treated in Comparative Example 2 exhibited significant breakage and fuzzing, resulting in severe dust accumulation on the fabric surface and a significantly worse dust-resistant effect compared to Example 1. This demonstrates that hydrophilic organic compounds containing hydroxyl groups are necessary to achieve the dust-resistant effect of this invention.

[0054] Comparative Example 3

[0055] The synthesis steps are basically the same as in Example 1, except that the molar ratio of the hydroxyl-containing hydrophilic organic compound (polyethylene glycol monomethyl ether, Mn≈350) to cyanuric chloride is adjusted to 2.0:1 (exceeding the range of 0.8:1 to 1.2:1 of this invention). Specifically, 18.5 g (about 0.1 mol) of cyanuric chloride is added to 120 mL of acetone, and the mixture is stirred and dispersed under conditions of cooling to 0-5 °C in an ice-water bath. Then, 70 g (about 0.2 mol) of polyethylene glycol monomethyl ether is slowly added dropwise to form a solution dissolved in 60 mL of acetone. The remaining steps are the same as in Example 1.

[0056] Observations revealed that the system exhibited significant gelation during the reaction, failing to form a uniformly dispersed finishing agent stock solution, making it unsuitable for subsequent finishing. This indicates that controlling the molar ratio of the hydroxyl-containing hydrophilic organic compound to cyanuric chloride within the range of this invention (0.8:1 to 1.2:1) is crucial for system stability and finishing effect.

[0057] As can be seen from the above embodiments, the specific finishing agent components of the present invention work synergistically, resulting in silk fabrics treated with them exhibiting significant anti-dust and anti-fragmentation effects. After multiple washes (good results after 10 washes), the fibrillation of fibers is greatly reduced, and the original hand feel of the fabric is well preserved. Furthermore, the finishing method for silk fabrics of the present invention is simple, releases no formaldehyde, and is safe and environmentally friendly.

[0058] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only for the purpose of helping to understand the method and core ideas of the present invention. The above descriptions are only preferred embodiments of the present invention. It should be noted that due to the limitations of textual expression, while there are objectively infinite specific structures, those skilled in the art can make several improvements, modifications, or changes without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner. These improvements, modifications, changes, or combinations, or the direct application of the inventive concept and technical solution to other situations without modification, should all be considered within the scope of protection of the present invention.

Claims

1. A finishing agent for preventing ash damage to silk fabrics, characterized in that, The raw materials for preparation include cyanuric chloride, hydrophilic organic compounds containing hydroxyl groups, and water-soluble organic solvents; The cyanuric chloride has a mass percentage concentration of 10%-30% relative to the water-soluble organic solvent; the water-soluble organic solvent is selected from one or more of acetone, dimethyl sulfoxide, tetrahydrofuran, and 1,4-dioxane. The hydroxyl-containing hydrophilic organic compound is selected from one or more of sodium p-phenolsulfonate, sodium glycolate, and oligomeric polyethylene glycol monomethyl ether; the molar ratio of the hydroxyl-containing hydrophilic organic compound to cyanuric chloride is 0.8:1 to 1.2:

1.

2. A method for preparing the anti-fouling finishing agent as described in claim 1, characterized in that, The process includes the following steps: dispersing cyanuric chloride in a water-soluble organic solvent, adding a hydroxyl-containing hydrophilic organic compound under stirring conditions to react and obtain the anti-scratching finishing agent.

3. A method for finishing silk fabrics, characterized in that, Includes the following steps: The anti-smudge finishing agent described in claim 1 is dispersed in water to form a finishing working solution, which is then applied to the silk fiber material to be treated. After finishing, the finished silk fabric is obtained.

4. The sorting method according to claim 3, characterized in that, The silk fiber material to be processed is an undyed fabric, a dyed fabric, or a printed fabric.

5. The sorting method according to claim 4, characterized in that, The finishing working solution is adjusted to pH 6-8, impregnated with the silk fiber material to be treated, and heated to 40-60℃ for finishing. After rinsing and drying, the finished silk fabric is obtained.